Frequency and prevalence of clinical conditions and therapeutic drugs used in dog and cat at Teaching Veterinary Hospital, Chattogram Veterinary and Animal Sciences University - Hasib, FM Yasir; Kabir, Md Hossain; Barua, Shanta; Akter, Sharmin; Chowdhury, Sharmin (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study was carried out to determine the frequency and prevalence of clinical conditions and their treatment, especially antibiotics in dogs and cats. Materials and Methods: A period of 12-month retrospective study was conducted at the Teaching Veterinary Hospital, Chattogram Veterinary and Animal Sciences University, Chittagong, Bangladesh from July 2018 to June 2019. A total of 849 cases, including 488(57.5%) and 361 (42.5%) dogs and cats respectively, were in account to espy the clinical conditions. Season, age, sex, and breed were the parameters to analyze the prevalence of those clinical conditions. Results: From the study, it was found that the endoparasitic infestation was highly frequent in both dog and cat (55% in dogs and 59% in cats). The endoparasitic infestation was highly prevalent in cats (91.53%) significantly (p = 0.003), which were ≤1 year of age. On the other hand, the ectoparasitic infestation was found prevalent significantly (p = 0.06) in the winter than any season and dewormed dogs (p = 0.03). Prevalence of canine parvovirus infection in dogs and wound in cats were substantially higher (p < 0.001 and p=0.05 respectively) in the winter whereas the prevalence of myiasis in dogs was prominent in the rainy season significantly (p = 0.01). The mostly used antibiotic was ceftriaxone (9.5% in dogs and 4% in cats). Conclusion: Different endoparasitic, ectoparasitic, and infectious diseases found prone to infect pet animals, mainly dogs, and cats. By maintaining proper anthelmintics and vaccine shots may act as a prevention procedure to those infections. J. Adv. Vet. Anim. Res., 7(1): 156-163, March 2020